2017
DOI: 10.1108/josm-11-2015-0370
|View full text |Cite
|
Sign up to set email alerts
|

Does one size fit all? New service development across different types of services

Abstract: Purpose-The extant new service development (NSD) literature tends to assume that the key practices for NSD identified in one context apply for all services, and has failed to sufficiently consider differences in NSD between service types. This study explores the nature of NSD across different service types. Design/methodology/approach-An extensive, cross-sectoral survey was conducted in seven countries. Data from 1333 NSD projects was analyzed to empirically derive a service typology and examine if and how dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 66 publications
(133 reference statements)
2
36
0
2
Order By: Relevance
“…This paper also shows that the use of IT tools becomes more difficult when the degree of the firm's servitization increases. This finding is in line with previous lines of argument in the service innovation context, namely that firms that apply IT tools face more difficulties, predominantly because the tasks are less structured and involve more stakeholders (e.g., Jaakkola et al, ; Johne and Storey, ). The data show that the likelihood of IT tools being applied—for both internal and external information flows—decreases when the service focus of the firm increases.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This paper also shows that the use of IT tools becomes more difficult when the degree of the firm's servitization increases. This finding is in line with previous lines of argument in the service innovation context, namely that firms that apply IT tools face more difficulties, predominantly because the tasks are less structured and involve more stakeholders (e.g., Jaakkola et al, ; Johne and Storey, ). The data show that the likelihood of IT tools being applied—for both internal and external information flows—decreases when the service focus of the firm increases.…”
Section: Discussionsupporting
confidence: 90%
“…The deep involvement of customers, employees, and service network partners impose significant demands on the organization to generate, process, and distribute information between and together with diverse stakeholders (e.g., Nijssen, Hillebrand, Vermeulen, and Kemp, ; Storey, Cankurtaran, Papastathopoulou, and Hultink, ; Wieland, Polese, Vargo, and Lusch, ). Regarding the use of IT tools, previous research has emphasized their importance for service innovations (e.g., Plattfaut et al, ), but has also identified several challenges, due to the heterogeneity of the stakeholders (Jaakkola, Meiren, Witell, and Reynoso, ). This implies that the use of IT and its performance impact cannot be independent from the firm's business focus.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, NSC is still not as well understood as NSD's back end, which tends to be structured more formally (Secomandi and Snelders, 2011). Our limited understanding of the NSC process is a significant concern because the production of promising, viable new service concepts is a determinant of NSD performance (Kelly and Storey, 2000;Magnusson et al, 2016), which in turn is a determinant of service provider success (Jaakkola et al, 2017;Papastathopoulou and Hultink, 2012). In short, a service provider's ability to produce new and innovative services hinges largely on its ability to conceive new services, even when its back-end capabilities are advanced (Patrício et al, 2011).…”
Section: New Service Conceptionmentioning
confidence: 99%
“…Levando isso em consideração, testou-se as relações entre os construtos, orientação para o cliente, competências profissionais e retenção de clientes, com a intenção de definir com maior precisão os consequentes que impactam no DNS. Neste horizonte, a literatura aponta que o aumento da orientação para o mercado, leva ao aprimoramento das capacidades de conexão com os clientes, fortalecendo os relacionamentos de longo prazo, enfatizando o aumento das habilidades dos profissionais no desenvolvimento e lançamento de novos produtos e/ou serviços, reforçando a capacidade da continuidade dos relacionamentos com os clientes (Sampaio, Perin& Ferreira, 2008 2 Modelo teórico e hipóteses de pesquisa É importante salientar que as práticas do DNS capturam como as empresas gerenciam o processo de desenvolvimento de novos serviços (Biemens et al, 2016;Jaakkola et al, 2017), destacando os processos mais formalizados como um fator de sucesso (Kuester et al, 2013). Outra função importante, diz respeito à forma como os dadod ou as informações dos clientes são coletadas, destacando o envolvimento do cliente no processo de criação de novos serviços (Edvardsson et al, 2012;Papastathopoulou & Hultink, 2012).…”
Section: Introductionunclassified